2021
DOI: 10.1128/aem.00593-21
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma reesei ACE4, a Novel Transcriptional Activator Involved in the Regulation of Cellulase Genes during Growth on Cellulose

Abstract: The filamentous fungus Trichoderma reesei is a model strain for cellulase production. Cellulase gene expression in T. reesei is controlled by multiple transcription factors. Here, we identified by comparative genomic screening a novel transcriptional activator ACE4 ( A ctivator of c ellulase e xpression 4) that positively regulates cellulase gene expression on cellulose in T. rees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…2 ), suggesting that it is necessary to enhance the expression of ACE3 beyond the upregulation by mutated XYR1 V821F . It was previously reported that ACE4 directly binds to the ace3 promoter and regulates ACE3 expression to promote cellulase production 56 . Possibly ACE3 is regulated not only by XYR1 but also by other factors, including ACE4, which suggests that enhanced expression of ACE3 by factors other than XYR1 may be the key to the cellulase expression.…”
Section: Discussionmentioning
confidence: 99%
“…2 ), suggesting that it is necessary to enhance the expression of ACE3 beyond the upregulation by mutated XYR1 V821F . It was previously reported that ACE4 directly binds to the ace3 promoter and regulates ACE3 expression to promote cellulase production 56 . Possibly ACE3 is regulated not only by XYR1 but also by other factors, including ACE4, which suggests that enhanced expression of ACE3 by factors other than XYR1 may be the key to the cellulase expression.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other filamentous fungi, A. nidulans is rarely used in the scaled-up production of industrial enzymes because of their low expression capacity. Trichoderma reesei is the main strain for cellulase production because of its excellent secretory ability [ 43 , 44 ]. However, the fermentation process of T. reesei usually takes up to a week.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, cellulase genes were regulated by different transcription factors. For example, in T. reesei , Xyr1 and ACEI can regulate the expression of the cellulase cbh1 gene, and ACE4 can regulate the expression of the cellulase gene by binding to the promoter of cellulase gene [ 52 , 53 ]. In this study, we also found that FfMYB15 could regulate the expression of cellulase gene, which indicated that MYB can also participate in the cellulose degradation mechanism, however, the mechanism of cellulose degradation has not been thoroughly studied.…”
Section: Discussionmentioning
confidence: 99%